Tics and disgust: An exploratory study - Ólafía Daðadóttir 1995-; Sigrún Edda Jónsdóttir 1995- (2019)
The objective of this study was to explore the relationship between tic-related behaviours and disgust. We use the term disgust proneness as an overarching construct containing two components; disgust propensity (general tendency to experience disgust) and disgust sensitivity (negative appraisal of experiencing disgust). Sensory phenomena (SP) is a broad term defining subjective experiences (e.g. feelings of incompleteness and not just right experiences (NJREs)) that precede repetitive behaviours such as tics in tic-related disorders and compulsions in Obsessive Compulsive Disorder (OCD). Recent findings suggest that NJREs and feelings of incompleteness mediate the relationship between disgust and OCD symptoms, washing compulsions in particular. Because SP is present in both OCD and tic-related disorders, it is possible that disgust proneness is related to tic-related behaviours as well. However, the authors of this report are not aware of any research on this topic. Questionnaires were administered in a sample of 279 students enrolled at the University of Iceland, to measure disgust proneness, tics, premonitory urges, symptoms of anxiety and depression and motivational dimensions associated with OCD. Mean age of the sample was 24.30 years (SD = 4.10). The results suggest that disgust is associated with both OCD symptoms and tic-related behaviours. The relationship between disgust and tic-related behaviours persists even when controlling for anxiety and depression. OCD and tic-related behaviours are suggested to have different underlying mechanisms. Further studies on the topic may help to explain the frequent comorbidity between these two conditions and the possible role of disgust proneness in the two.